Microsimulation and clinical outcomes analysis support a lower age threshold for use of biological valves. Issue 21 (18th October 2010) - Stoica, Serban; Goldsmith, Kimberley; Demiris, Nikolaos; Punjabi, Prakash; Berg, Geoffrey; Sharples, Linda; Large, Stephen
Abstract : Objective: To characterise contemporary results of aortic valve replacement in relation to type of prosthesis and subsequent competing hazards. Methods: 5470 procedures in 5433 consecutive patients with aortic valve replacement ± coronary artery bypass grafting (CABG) were studied. Microsimulation of survival and valve-related outcomes was performed based on meta-analysis and patient data inputs, with separate models for age, gender and CABG. Survival was validated against the UK Heart Valve Registry. Results: Patient survival at 1, 5 and 10 years was 90%, 78% and 57%, respectively. The crossover points at which bioprostheses and mechanical prostheses conferred similar life expectancy (LE) was 59 years for men and women (no significant difference between prosthesis types between the ages of 56 and 69 for men, and 58 an 63 for women). The improvement in event-free LE for mechanical valves was greater at younger ages with a crossover point of 66 years for men and 67 years for women. Long-term survival was independently influenced by age, male gender and concomitant CABG, but not by type of prosthesis. In bioprostheses the most common long-term occurrence was structural deterioration. For men aged 55, 65 and 75 at initial operation it had a lifetime incidence of 50%, 30% and 13%, respectively. The simulation output showed excellent agreement with registry data. Conclusion: Bioprostheses can be implanted selectively in patients as young as 56 without significant adverse effects on life expectancy, although event-free life expectancy remains significantly lower with bioprostheses up to age of implant of 63.